Multilingual Email Zoning - Segmenting Multilingual Email Text Into Zones - Jardim, João Bruno Morais de Sousa (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence